The Effect of Communication and Work Discipline on Worker Performance Among Freelance Workers in a Work-from-Home Environment: Evidence from Forkey Creative Agency - Yudiyanto Joko Purnomo; Salsabila Shofiyah (PT. LITERASI SAINS NUSANTARA, 2026)
This study aims to examine the effects of communication and work discipline on worker performance among freelance workers operating under a Work from Home (WFH) system at Forkey Creative Agency in Bandung. A quantitative approach with a descriptive-associative design was employed. The study involved 30 freelance workers who had worked at the agency for more than one year, with a census sampling technique. Data were collected using a five-point Likert-scale questionnaire and analyzed through multiple linear regression after validity, reliability, and classical assumption tests. The results indicate that communication has a positive and significant effect on worker performance, while work discipline also has a positive and significant effect. Work discipline demonstrates a stronger relative contribution than communication. Furthermore, communication and work discipline simultaneously have a significant effect on worker performance, with an R² value of 0.951. These findings highlight the importance of effective communication and disciplined work behavior in supporting freelance worker performance within a remote working environment.